ANALISIS PENERAPAN CUSTOMS VALUATION DAN TRANSFER PRICING DALAM TRANSAKSI PARA PIHAK YANG MEMILIKI HUBUNGAN ISTIMEWA - Hasyim Azhari; Mohammad Fachrudin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Indonesia is ranked the 9th largest developing country with illicit financial flows with anaverage of USD 18,071 billion per year and ranked 8th with the highest trade missinvoicing over the period 2004 - 2013 with gross trade miss invoicing of USD 590.941billion. (Global Financial Integrity, 2015). The relationship between transfer pricing andcustoms valuation has been discussed in various national and international forums inrecent years. The purpose of this study is to analyze the relationship between customsvaluation for the calculation of import duties and transfer pricing carried out bymultinational companies in Indonesia. This study uses a qualitative method. The type ofdata used in this study is secondary data in the form of books, journals, or written worksthat can be obtained through literature studies and interviews with regulators,practitioners, and academics. The results of the study show that there are similaritiesbetween customs valuation and transfer pricing, namely they both use the concept of thearm's length principle in setting a "fair price" and there are differences in focus andimportance between customs valuation and transfer pricing. The transfer pricingadjustment at the end of the fiscal year can significantly affect the validity of the customsvalue of the goods concerned..